Community Empowerment through an Inclusive Literacy Movement based on Learning Communities in Butta Ejayya Village, Gowa - Nur Riswandy Marsuki; Memunah Memunah; Sitti Asnaeni; St. Haniah; Nurbaeti Nurbaeti; Muhsin Muhsin (CV. Dharma Samakta Edukhatulistiwa, 2026)
The problem of low literacy rates and the persistence of illiteracy pose serious challenges to community empowerment efforts, particularly in rural areas. This Community Service (PkM) activity aims to empower the community through an Inclusive Literacy Movement based on a learning community in Butta Ejayya Village, Gowa Regency. The approach used was participatory and inclusive, involving the community as the main subject in the planning, implementation, and evaluation processes of the activity. The implementation method included identifying the community's literacy needs, establishing a learning community, mentoring reading and writing activities, and strengthening the role of local leaders as literacy drivers. The results of the activity showed increased community participation in literacy activities, growing awareness of the importance of reading and writing skills, and the formation of a learning community as a space for continuous shared learning. This activity also contributed to strengthening the community's social capacity and became the first step in eradicating illiteracy. Thus, the inclusive literacy movement based on a learning community has proven effective as a community empowerment strategy and can be replicated in other areas with similar characteristics.